2018
DOI: 10.1371/journal.pone.0206556
|View full text |Cite
|
Sign up to set email alerts
|

Modelling digestive hydrolysis of nutrients in fish using factorial designs and desirability function

Abstract: Models simulating the in vitro digestive hydrolysis of nutrients by different animal species are frequently used to obtain a better understanding of factors affecting this process. Optimization algorithm of a model may be used to prospect the more favourable combination of selected factors resulting in the higher performance. This study was conducted to determine the combination of factors (pH, enzyme:substrate ratio, and reaction time) leading to highest bioavailability of proteins and carbohydrates in the gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
(64 reference statements)
1
16
0
1
Order By: Relevance
“…In the present study, the higher pentoses and amino acids release observed in the alkaline stage may have been triggered by the previous stomach digestion, which facilitated protein and carbohydrate hydrolysis during intestinal digestion by increasing substrate accessibility to the enzymes. Similarly, other authors also observed that the acid pre-digestion of fishmeal and plant feedstuffs increased intestinal protein hydrolysis 27 , 59 , reflecting the significant contribution of alkaline digestion in the total protein hydrolysis 60 .…”
Section: Discussionmentioning
confidence: 60%
“…In the present study, the higher pentoses and amino acids release observed in the alkaline stage may have been triggered by the previous stomach digestion, which facilitated protein and carbohydrate hydrolysis during intestinal digestion by increasing substrate accessibility to the enzymes. Similarly, other authors also observed that the acid pre-digestion of fishmeal and plant feedstuffs increased intestinal protein hydrolysis 27 , 59 , reflecting the significant contribution of alkaline digestion in the total protein hydrolysis 60 .…”
Section: Discussionmentioning
confidence: 60%
“…The alkaline digestion plays a predominant role in the complete protein breakdown in gastric fish and non‐gastric fish (Gilannejad et al 2018). Knowledge of the activity of alkaline proteases, present in the digestive tract of fish, is very important since non‐gastric fish or fish that do not yet have a developed and functional stomach, they are solely responsible for the digestion of dietary proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between two fish developmental stage [ 166 ] 3.5 & 8 6.25 37 15 & 45 Soybean concentrate on 7 different level DH, Nutrient retention (N, P), Invivo Totaba magnodali [ 83 ] 8 nd 25 60 min Nannochloropsis granulata DH Oncorhynchus mykiss Litopenaeus vannamei Evaluate different treatment by supercritical CO 2 extraction [ 167 ] 3.5–6.5 & 6.5–8.5 125–500 & 50–200 nd. 240–480 & 480–640 Comerical feed FAA Reducing sugar Sparus aurata Two stage membrane reactor, with fish crude extract [ 23 ] 3.5 & nd. nd.…”
Section: Application Of In-vitro Digestion Model I...mentioning
confidence: 99%
“…The in-vitro digestion studies for human has been applied throughout several different applications ( Figure 1 ). Moreover, they were well documented with several globally practiced protocols, while the protocols for fish was limited and highly varied between different authors [ 23 ]. Both fish and humans are monogastric vertebrates, sharing a similar gastrointestinal tract with differences in the anatomical, physiological, and enzymatic features.…”
Section: Introductionmentioning
confidence: 99%